Penerapan Problem Based Learning untuk Meningkatkan Kemandirian Belajar Siswa SMK - Murti, Setyo Ranu; Umam, Nur Khotibul; Saputro, Ida Nugroho; Kurniawati, Etiek (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
In the current era, students are required to be able to adapt, think critically, and be able to learn independently. This study aims to improve students' learning independence at the vocational high school level, especially in class XI DPIB SMK Ganesha Tama Boyolali by implementing the Problem Based Learning model in the Expertise Concentration subject. This study is a Classroom Action Research with a research design using the Kemmis & McTaggart model. The research subjects used were 27 students of class XI DPIB SMK Ganesha Tama Boyolali. Data collection techniques were obtained through observation, documentation and field notes. The collection was carried out through two cycles and one pre-cycle. Data analysis used is a descriptive analysis technique sourced from the results of observations. The results of the observations showed an increase in learning independence from 37.0% in the pre-cycle, 55.6% in the first cycle, and 77.8% in the second cycle. Students showed positive developments in aspects of initiative, responsibility, perseverance, and confidence in completing tasks. The implementation of the PBL model has been proven effective in increasing student learning independence at SMK Ganesha Tama Boyolali.Dalam era saat ini, siswa dituntut untuk dapat beradaptasi, berpikir kritis, dan mampu belajar secara mandiri. Penelitian ini bertujuan untuk meningkatkan kemandirian belajar siswa pada jenjang SMK khususnya di kelas XI DPIB SMK Ganesha Tama Boyolali dengan menerapkan model Problem Based Learning dalam mata pelajaran Konsentrasi Keahlian. Penelitian ini merupakan Penelitian Tindakan Kelas dengan desain penelitian menggunakan model Kemmis & McTaggart. Subjek penelitian yang digunakan adalah siswa kelas XI program keahlian DPIB di SMK Ganesha Tama Boyolali berjumlah 27 siswa. Teknik pengumpulan data didapatkan melalui observasi, dokumentasi dan catatan lapangan. Pengambilan dilakukan melalui dua siklus dan satu pra-siklus. Analisis data yang digunakan adalah teknik analisis deskriptif yang bersumber dari hasil observasi. Hasil observasi menunjukkan peningkatan kemandirian belajar dari 37,0% pada pra-siklus, 55,6% pada siklus pertama, dan 77,8% pada siklus kedua. Siswa menunjukkan perkembangan positif dalam aspek inisiatif, tanggung jawab, ketekunan, serta kepercayaan diri dalam menyelesaikan tugas. Penerapan model PBL telah terbukti efektif dalam peningkatan kemandirian belajar siswa di SMK Ganesha Tama Boyolali.